A new contact algorithm in the material point method for geotechnical simulations. (18th March 2014) - Ma, J.; Wang, D.; Randolph, M.F.
SUMMARY Contact between stiff structural elements and soil is encountered in many applications in geotechnical engineering. Modelling of such contact is challenging as it often involves impact that would lead to large deformation and failure of the soil. The Material Point Method (MPM) is a mesh‐free method that has been applied to simulate such phenomena. However, the frictional contact algorithm commonly used in MPM only supports Coulomb friction and cannot model fully or partially rough contact conditions in terms of geotechnical engineering. Moreover, because of very different stiffness of contacting materials, the contact force predicted by the previous frictional contact algorithms usually suffers from severe oscillation when applied in structure–soil interaction. This paper presents a new contact algorithm, termed Geo‐contact, designed for geotechnical engineering. In Geo‐contact, a penalty function is incorporated to reduce the oscillation in contact computation, and a limited shear stress is specified along the contact interface. The proposed Geo‐contact algorithm has been implemented to simulate smooth, partially rough and rough contact in typical large deformation penetration problems. The resistance–displacement curves obtained using the Geo‐contact are compared with analytical solutions of limit analysis and large deformation finite element results to verify the accuracy and robustness of the proposed contact algorithm. Copyright © 2014 John Wiley & Sons, Ltd.